Do Financial Performance And Firm Value Can Improve Corporate Responsibility Disclosure? - Dini Wahjoe Hapsari, Willy Sri Yuliandhari, M. Fadel Variza (Jurnal Manajemen, 2019)
The aims of this research are to find out how the effect of financial performance is proxied by ROA and ROE on the firm value which is proxied by Tobin's Q with CSR that is proxied by cost allocation as moderating the plantation sub-sector listed on the Indonesia Stock Exchange for the period of 2013-2016. This research will seek the causes of whether CSR data allocation is able to strengthen or weaken the influence of financial performance on firm value. The sampling technique used was purposive sampling, and eight companies were selected as samples of plantations with a four-year research period to obtain 32 sample units. The analytical method used is descriptive statistical testing, panel data regression analysis and moderated regression analysis (MRA) using e-views software 9.0 versions. Based on the result of the test, the financial performance variables that are proxied by ROA and ROE partially and simultaneously have a significant positive effect on firm value. While the MRA showed that CSR weakens the relationship between financial performance and company value. Based on the result that the companies and investors need to pay attention to the composition of financial performance and disclosure of corporate social responsibility, hence the investor is able to minimize the risks that will be borne when investing their capital.